Changing epidemiology of patients treated with direct acting antivirals for HCV and persistently high SVR12 in an endemic area for HCV infection in Italy: real-life 'LIver Network Activity' (LINA) cohort update results. (2nd September 2021) - Scotto, Riccardo; Buonomo, Antonio Riccardo; De Pascalis, Stefania; Nerilli, Mariagiovanna; Pinchera, Biagio; Staiano, Laura; Mercinelli, Simona; Cattaneo, Letizia; Stanzione, Maria; Stornaiuolo, Gianfranca; Martini, Salvatore; Messina, Vincenzo; et al.
ABSTRACT: Background: Second generation direct acting antivirals (DAAs) drastically changed the landscape of chronic HCV (CHCV). Aim of this paper was to assess the effectiveness of DAAs, also looking at the demographic characteristics of subjects enrolled. Research design and methods: Ambispective multi-center real-life study conducted among patients with CHCV treated with DAAs in Campania Region (Southern Italy). Patient were enrolled in two cohorts according to time of enrolment. Results: 1, 479 patients were enrolled. Patients aged ≥60 years were 74.7% in the historic cohort (953 patients) and 70.2% in the prospective cohort (526 patients. Patients aged ≥ 60 years showed a higher prevalence of genotype 1b (p<0.001) and 2 (p<0.001), while patients aged < 60 years showed a higher prevalence of genotype 1a (p<0.001), 3 (p<0.001) and 4 (p<0.05). SVR12 was 98.5% in both cohorts. SVR12 was similar among patients of the prospective cohort aged < and ≥ 60 years (99.4% vs 98.1%). SVR12 among patients with and without cirrhosis was 96.0% and 98.9%, respectively. Conclusions: DAAs provide high efficacy also in harder to treat patients. The effectiveness of DAAs is leading to a shift in patients characteristics with a greater prevalence of younger subjects and persons with mild liver disease.